Tuturan Ekspresif Ichiro Suzuki terhadap Petutur Anak dan Remaja dalam Serial Video “Oshiete! Ichiro Sensei” - Komang Ayu Nuriasih; Anak Agung Ayu Dian Andriyani; Ni Wayan Meidariani (Omiyage : Jurnal Bahasa dan Pembelajaran Bahasa Jepang, 2022)
This research aims to describe the expressive function of Ichiro Suzuki’s utterances in a Japanese video series titled “Oshiete! Ichiro Sensei”, which involves various ages of speech act participants including children and teenagers. On the basis of variative situational context surrounding the utterances, especially in accordance with Ichiro Suzuki’s background knowledge and personal experience, this research is important to be conducted in order to minimalize a misconception in understanding a Japanese’s utterances which happen to not always represent the common image of Japanese in terms of communication. This research uses the descriptive qualitative method with Pragmatic Identity Method as its analyzing tool. The result of this research shows that Ichiro Suzuki’s expressive utterances towards the children and teenagers aim to tease, to compliment, to agree, to show admiration, to show embarrassment, and to show confidence; all of which are delivered through direct utterances. In particular, this research underlines the distance between Ichiro Suzuki and the speech act participants as the main factor on the use of such direct utterances.